Analisa Campuran CPHMA terhadap Penambahan Variasi Aspal Penetrasi 60/70 pada Karakteristik Marshall - Suciati, Herlina; Simamora, Afri Wijaya; Panusunan, Panusunan; Fauzan, Fauzan (Jurnal Teknologi Riset Terapan, 2023)
Purpose: Highways are one of the main infrastructures in the country's development. On remote and outermost islands there are access barriers to asphalt pavement units (amps). The application of CPHMA (Cold Paving Hot Mix Asbuton) technology is one of the main options to overcome this problem. Methodology: The test showed that asphalt content from 0.5% to 2.0% improved stability and met flow requirements, while 2.5% exceeded flow limits and reduced stability. Result: The test results for other Marshal characteristics namely MQ, VFB, VIM, and VMA meet the specifications used. At the addition of asphalt content of 0.5% - 2.5%, the values of MQ, VFB, and VMA increased along with the increase in the addition of asphalt content. On the other hand, the VIM value decreased with increasing asphalt content. From the test results, it is known that the optimum penetration value of asphalt 60/70 is 1.25%. Conclusion: Adding 60/70 penetration asphalt at 0.5%–2.0% improves Marshall characteristics, with an optimal content of 1.25%. Limitation: Tests were limited to laboratory conditions and did not reflect actual traffic performance. Contribution: This study provides practical recommendations for enhancing CPHMA performance using 60/70 asphalt